Antibiotic resistance of Helicobacter pylori in the Peruvian population: a systematic review and meta-analysis of its prevalence in the general population - Villavicencio Saque, Rodrigo (2023)
Helicobacter pylori infection is quite common worldwide and is associated with gastric adenocarcinoma. The high rates of resistance found in Latin American countries justify the investigation of local resistance rates, which could improve the therapeutic approach and eradication rates. The objective is to evaluate the prevalence of resistance in Peru of Helicobacter pylori to commonly used antibiotics. All studies in the Peruvian population that revealed rates of antibiotic resistance of Helicobacter pylori were included. A systematic literature search was conducted up to January 2021, using PubMed and other databases. For the group of patient studies with the EUCAST cut-off point, the resistance was as follows: Amoxicillin 14% (95% CI: 6-25), Clarithromycin 43% (95% CI: 30-57), Metronidazole 58% (95% CI: 22-90) and 51% Quinolones (95% CI: 38-64). For the EUCAST cut-off group of sample studies, the following: Amoxicillin 57% (95% CI: 51-63), Clarithromycin 35% (95% CI 30-41), Metronidazole 67% (95% CI: 62-72) and 4% Tetracycline (95% CI: 2-7). A high antibiotic resistance of Helicobacter pylori was found in most of the groups studied, although with heterogeneity between the studies. The rate of resistance to tetracyclines was low and the studies were shown to be homogeneous.